Simulation of Mechatronic Systems using Behavioural Hybrid Process Calculus - Krilavičius, T. (Elektronika ir Elektrotechnika, 2008)
The growing interest in hybrid systems both in computer science and control theory has generated an interest in formalisms that can be used to specify and analyse such systems, systems that combine continuous-time and discrete behaviours. Simulation is one of the tools to obtain insight in dynamical systems behaviour. Its results provide information on performance of system, are helpful in detecting potential errors, and are handy in choosing adequate control strategies and parameters. We report a work in progress, a technique and a prototype for simulation of Behavioural Hybrid Process Calculus, an extension of process algebra suitable for the modelling and analysis of hybrid systems. Ill.1, bibl. 20. (in English; summaries in English, Russian and Lithuanian).